Effects of phenolic compounds on the sulfidogenic activity of Desulfotomaculum sp. and Desulfovibrio desulfuricans bacteria - Verkholiak, Natalіa; Peretyatko, Taras; Halushka, Andrii (Ecological Questions, 2021)
Purification of environment from the pollutants of organic and inorganic matter is one of the actual problem of nowadays. Compounds with benzene ring are among the most hazardous pollutants. The danger of getting the phenolic compounds into the environment is connected with their toxicity for biological objects and stability. One of the most effective methods of environment detoxification is the usage of microorganisms. The aim of this work was to determine the ability of Desulfotomaculum sp. AR1 and Desulfovibrio desulfuricans Ya-11 bacteria to utilize phenol derivatives as the carbon source and to study the effects of phenolic compounds on the sulfidogenic activity of these bacteria. Both bacterial strains grew in the media with pyrogallol and hydroquinone, but the biomass in the medium with hydroquinone was considerably lower. Inhibition of sulfate ion utilization by bacteria was found during the growth of Desulfotomaculum sp. AR1 and D. desulfuricans Ya-11 in the medium with phenolic compounds. Effectiveness of pyrogallol utilization by both bacterial strains was for 4 times higher, compared to the effectiveness of hydroquinone utilization. Desulfotomaculum sp. AR1 and D. desulfuricans Ya-11 bacteria are also capable for growth in the medium with sodium benzoate, utilizing this aromatic compound as carbon and energy source. Process of catechol degradation by Desulfotomaculum sp. AR1 bacteria under anaerobic conditions is ineffective. Desulfotomaculum sp. AR1 and Desulfovibrio desulfuricans Ya-11 bacteria are capable for growth in the medium with phenolic compounds, utilizing them as the sole carbon source and removing them from the environment. ANOVA showed significant differences between the amount of utilized SO42- in the control medium and medium with aromatic compounds. Presence of aromatic compounds in the medium inhibits the sulfate reduction in Desulfotomaculum sp. AR1 and D. desulfuricans Ya-11 bacteria, which results in the decrease of toxic hydrogen sulfide accumulation in the medium. Usage of microorganisms with the aim of environment detoxification is a promising way of water biotopes remediation technologies.